ANAEMIA IN PREGNANCY: THE IMPACT ON MATERNAL AND FETAL HEALTH, INNOVATION, AND MANAGEMENT IN KEDUNGJATI PRIMARY HEALTH CARE - Alexandria Firdaus Al-Farisy (Jurnal Medika Malahayati, 2023)
Anaemia is a common condition affecting a significant proportion of pregnant women worldwide, particularly in low- and middle-income countries. Anaemia is associated with adverse outcomes for both the mother and the developing fetus, including increased risk of preterm birth, low birth weight, and maternal mortality. Primary health care settings play a crucial role in the identification, management, and prevention of Anaemia in pregnant women. This review aims to provide an overview of the prevalence and impact of Anaemia on maternal and fetal health, as well as the current approaches to its management in primary health care settings. We conducted a comprehensive search of electronic databases for relevant studies published between 2010 and 2021, including systematic reviews, meta-analyses, and clinical practice guidelines. The results indicate that the prevalence of Anaemia in pregnancy varies widely depending on the population and the diagnostic criteria used, with rates ranging from 20% to 80%. Anaemia is associated with a range of adverse maternal and fetal outcomes, including increased risk of preterm birth, low birth weight, and maternal mortality. The management of Anaemia in primary health care settings involves a multifaceted approach, including iron and folic acid supplementation, dietary and lifestyle modifications, and close monitoring of maternal and fetal health. While the evidence base for the management of Anaemia in primary health care is relatively strong, there is a need for further research on the effectiveness and cost-effectiveness of interventions, as well as strategies to improve the identification and management of Anaemia in pregnant women.